2019
DOI: 10.29252/aassjournal.7.1.57
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Culture in Sports Sponsorship: an Update

Abstract: Nowadays sponsorship is an important part of sports events. Sports sponsorship offers more benefits, more variety and also it's a more powerful form of marketing. In general, sponsorship holds a unique position in the marketing mix because it is effective in building brand awareness, provides different marketing platforms and valuable networking and hospitality opportunities. Sponsorship marketing efforts can be influenced by culture. Especially when global sponsorship in sports which refers to sports events i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 67 publications
(67 reference statements)
0
9
0
5
Order By: Relevance
“…It has the power to inspire. It has the power to unite people in a way that no one else does [28]. For Indonesian people in general, sport is not yet a good opportunity to guarantee life.…”
Section: Interpreting Sports In the Culture Of Islamic Society In mentioning
confidence: 99%
“…It has the power to inspire. It has the power to unite people in a way that no one else does [28]. For Indonesian people in general, sport is not yet a good opportunity to guarantee life.…”
Section: Interpreting Sports In the Culture Of Islamic Society In mentioning
confidence: 99%
“…Erdogan and Kitchen (1998) add that sponsorship is a practice promotes the company and its brand interests by connecting with an important event for society. The sponsorship has many types such as cash, physical or logistical payments provided by the company to the sponsored team and in a different way of the original mission of such company in the marketplace (Keshkar et al, 2018) so sports sponsorship is an interdependence relationship involves some commercial benefits for all parties in the contract include commercial benefits to the sponsor and financial benefits to the sponsored team (Cruz, 2018).…”
Section: Brand Enhancement and Buying The Brandmentioning
confidence: 99%
“…In a study examining the effect of sports advertising and its association with viewing sporting events, he concluded that not only sports advertising would be highly effective but also the impact of sports advertising on the group of people who watch sports events is higher (42). In general, sporting events provide tremendous opportunities for companies to introduce their brands and products through advertising (43) and because attention is one of the most important factors in the success of a company or brand, we are looking at whether sport alone can influence people's attention, and, more importantly, does sports advertising have more power to attract people's attention than non-sports advertising and has the potential to bring the benefits of the brand (retention and increased shopping) to the company? In this regard, there is a gap in the literature where sport and non-sport advertising were compared.…”
Section: Introductionmentioning
confidence: 99%